Engineering mechanics : statics - Boresi, Arthur Peter. (Brooks/Cole, 2001)
This book is about: Review of concepts in mechanics; Forces and other vector quantities; Equilibrium of a particle; Two-Dimensional forces; Three-dimensional forces; Trusses; ...